P–459 Ex vivo perfusion of whole ewe ovaries with follicular maturation for up to seven days: towards the development of an alternative fertility preservation method. (6th August 2021) - Tsiartas, P; Mateoiu, C; Deshmukh, M; Banerjee, D; Padma, A; Jar-Allah, T; Akyürek, L; Khatibi, A; Milenkovic, M; Gandolfi, F; Hellström, M; Patrizio, P; et al.
Abstract: Study question: To develop an alternative fertility preservation method for young female cancer patients based on an ex vivo perfusion of whole ovaries serving as a platform for future ovarian stimulation studies. Summary answer: It is possible to maintain viable follicles and to retrieve oocytes after ex vivo perfusion of ewe ovaries for up to 7 days. What is known already: Some progress has been made in terms of follicular growth and the isolation of mature oocytes in vitro. However, full development, from early follicular stages to a viable offspring, has only been described in rodent models. The complex events controlling follicular expansion and the long time required for folliculogenesis and oocyte maturity in large mammalian species creating challenges and limitations for in vitro studies. Ex vivo perfusion of a whole ovary could potentially be a solution by exploiting the intact ovarian architecture to support folliculogenesis and oocyte maturation. Study design, size, duration: Thirty-one ewe ovaries were divided into 4 groups and ex vivo perfused in a bioreactor. Group 1 (n = 14) perfusion for 48 hours with no hormone supplementation; Group 2 (n = 4) perfusion 96–101 hours with follicle stimulating hormone (FSH); Group 3 (n = 3) perfusion 120–168 hours with human menopausal gonadotropin (hMG); Group 4 (n = 10) perfusion 72–144 hours with hMG. Participants/materials, setting, methods: Ewe ovaries from sexually mature ewes were ex vivo perfused in a bioreactor under normothermic conditions for up to 7 days (max total 168 hours). Histomorphological, immunohistochemical, hormonal and biochemical analyses were performed to assess ovarian structure and viability after cold ischemia and after perfusion which was subsequently compared to control ovaries. Main results and the role of chance: The perfused ovaries in group 2 and 3 showed no significant differences in follicular density, viability and oocyte quality after ischemia and perfusion compared to control ovaries. Estradiol and progesterone levels did not increase during the perfusion. The perfused ovaries in group 1 and 4 showed a significant decrease in the ovarian reserve and oocyte quality. In total, 16 GV-MI oocytes were retrieved from groups 3 and 4. Limitations, reasons for caution: 1. Ovaries were retrieved from ewes of unknown cycle and reproductive history. 2. The perfusion medium was changed after 24 hours from perfusion start to remove detrimental metabolites and this could affect the measured concentrations of hormones and metabolites in the perfusion medium. Wider implications of the findings: These results pave the way to propose ex vivo perfusion as a good platform for fertility preservation studies on whole mammalian and human ovaries to retrieve fully mature oocytes. Trial registration number: Not applicable